2015
DOI: 10.35362/rie672253
|View full text |Cite
|
Sign up to set email alerts
|

La formación para la innovación en España: situación, características y perspectivas de eficacia

Abstract: Los procesos de innovación son claves para las organizaciones, y la formación tiene un papel destacado en ellos. No obstante, en la literatura científica es difícil encontrar las características de la formación que acompaña la innovación. En este artículo se presentan los resultados de un estudio cuyos objetivos eran: identificar las características de la formación para la innovación, analizar su eficacia, describir casos de éxito y elaborar propuestas de mejora.La metodología del estudio fue mixta. Se realizó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Pineda Herrero et al . () found that training in areas such as creativity, managing change and technical skills was important for managing innovation.…”
Section: Academic Research Into Training and Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Pineda Herrero et al . () found that training in areas such as creativity, managing change and technical skills was important for managing innovation.…”
Section: Academic Research Into Training and Developmentmentioning
confidence: 97%
“…Expenditure on training and the formal organization of the training process contributed to company financial turnover (Marin-Diaz et al, 2014). Pineda Herrero et al (2015) found that training in areas such as creativity, managing change and technical skills was important for managing innovation.…”
Section: Improving Training For the Unemployedmentioning
confidence: 99%